Marmota (Marmota) camtschatica subsp. camtschatica Pallas 1811 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Marmota (Marmota) camtschatica subsp. camtschatica Pallas 1811 Marmota (Marmota) camtschatica subsp. camtschatica Pallas 1811, Zoographia Rosso-Asiatica: 156. Type Locality: " Kamchatka " [Kamchatsk. Obl., Russia]. Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Rodentia - Family Sciuridae, pp. 754-818 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 2, Baltimore :The Johns Hopkins University Press on page 800, DOI: 10.5281/zenodo.7316535